Oil-in-water emulsion as a modifier of water reflectance - Otremba, Zbigniew (Oficyna Wydawnicza Politechniki Wrocławskiej, 2009)
The paper presents a component of the water reflectance in the visible region, stimulated by oil-in-water emulsion in the concentration of 1 ppm. A proxy for reflectance which is in use in oceanic optics has been studied. A significant change in reflectance for water contaminated by oil emulsion is revealed. In general, the reflectance generated by oil emulsion grows with light wavelength increase and in cases when small oil droplets dominate in oil-emulsion.
Optica Applicata, Vol. 39, 2009, nr 1, s. 123-128
Keywords: optyka; water; reflectance; spectra; oil; emulsion